Effect of Public Ownership Structure, Capital Structure, and Credit Risk on Profitability in Foreign Exchange National Private Commercial Banks - Surayya Surayya; Juliana Kadang (Budapest International Research and Critics University, 2022)
This study aims to determine and analyze the effect of public ownership structure, capital structure, and credit risk on profitability in Foreign Exchange National Private Commercial Banks. This type of research uses a quantitative descriptive method. The types and sources of data used in this study are secondary data. The total population in the study is 35 Foreign Exchange National Private Commercial Banks. The number of samples in this study are 17 Banks. The data analysis technique in this study uses statistical data using SPSS 21 software. Data analysis in this study uses panel data where the data is a combination of time series data. The results show that simultaneous test (F), namely public ownership structure, capital structure, and credit risk have significant effect on profitability in Foreign Exchange National Private Commercial Banks. The partial test (t) show that public ownership structure has significant effect on profitability in Foreign Exchange National Private Commercial Banks, capital structure has no significant effect on profitability in Foreign Exchange National Private Commercial Banks, and credit risk has significant effect on profitability in Foreign Exchange National Private Commercial Banks.